An oscillatory radiating hydromagnetic internal heat generating fluid flow through a vertcal porous channel with slip and temperature jump - Titiloye, Emmanuel Olurotimi; Gbadeyan, J.A.; Adeosun, Adeshina Taofeeq (Zielona Góra: Uniwersytet Zielonogórski)
The present study concerns the natural convective heat generating/absorbing, radiative magnetohydrodynamic, oscillatory fluid flow through a vertical porous channel with slip and temperature jump. The effect of Joule dissipation is taken into consideration while it is assumed that the flow is fully developed. The differential transforms method(DTM) is employed to solve the system of non-linear ordinary differential equations that is obtained from the non-linear partial differential equations governing the flow.
Keywords: temperature jump; velocity slip; hydromagnetic; oscillatory and porous channel